Minat Nasabah Non Muslim Dalam Membeli Produk Asuransi Syariah (Studi Kasus Pada Asuransi Jiwa Syariah Bumiputera 1912 Cabang Medan) - Damayanti, Ayu; Atika, Atika (Jurnal Manajemen Akuntansi (JUMSI), 2021)
Sharia life insurance is risk management based on the correct principles of assisting and protecting one another by making payments based on the death or life of the spouse or other payments stipulated in the contract at a fixed time to the spouse or other entitled party. Determined based on the results of fund management. Insurance two types of traditional life insurance and Sharia life insurance were introduced, where a fixed rate system traditionally upsets the conscience of all Muslims except in Indonesia. Interest in fiqh is classified as interest, which is prohibited by Sharia (Haram by law). Therefore, interest-free financial institutions, one of which is Sharia Life Insurance.